The Electoral Participation of Immigrants in Local Elections in Chile from 2012 to 2021 [la Participación Electoral de Los Inmigrantes en Las Elecciones Locales de Chile Entre 2012 y 2021 - Palomera-Valenzuela, A (Universidad Nacional de Colombia, 2024)
There is a broad debate about extending citizenship rights to the migrant population. Chile is unique for its inclusive institutional policy, under which immigrants have the right to vote after five years of residency and are automatically registered on the electoral roll. Significant progress has been made in understanding immigrant electoral participation; but studies usually focus on national elections, leaving local elections in the background. We argue that it is precisely in single-member municipal elections with majoritarian electoral systems where the immigrant vote can determine the result of an election: What does immigrant participation depend on? To what extent do immigrants’ gender and age explain their participation? In which municipalities might the immigrant vote be most decisive? We answer these questions reaching three conclusions. First, we find a gender gap in immigrant turnout in favour of women. Second, we find that the quadratic effect of age on turnout is weaker in the immigrant group than in the native group. Third, we propose an index of immigrants’ municipal incidence (IMIM), which allows us to identify the municipalities most likely to define their mayoral elections according to the size of the immigrant population. © 2024, Universidad Nacional de Colombia. All rights reserved.